Current Use of Intravenous (IV) Long Acting Antibiotic (LAA) Therapy in the Aetna Health Plan among Patients with Acute Bacterial Skin and Skin Structure Infection (ABSSSI). (4th October 2017) - Mehta, Rajesh; Edwards, Alison; Keyloun, Katelyn R; Bonine, Nicole; Juster, Iver
Abstract: Background: In an effort to lower costs and improve quality of care, there is potential to change the treatment landscape for low-risk (i.e., less severe) ABSSSI patients who historically required inpatient management, a costly option. Outpatient IV treatment pathways have been shown to be a cost-saving option for hospitals and insurers. The objective was to quantify the potential opportunity for reducing cost of ABSSSI treatment in an insured Commercial and Medicare Aetna population. Methods: Adult patients between January 2013 and July 2016 were identified with a primary ABSSSI claim (Table 1) in the Aetna fully-insured Commercial and Medicare insurance claims database. ABSSSI encounters were identified with insurance eligibility for the 7 months prior to and no evidence of ABSSSI in the 30 days prior to the ABSSSI claim. Demographic and clinical data were described, including length of stay (LOS) and allowed cost for inpatient encounters with data. Inpatient encounters without evidence of severity (e.g., codes for major complications or comorbidities) were considered potential candidates for an outpatient LAA pathway. A sensitivity analysis for LOS and cost was run including all ABSSSI patients with LAA dispenses through 2016 (i.e., inclusion/exclusion criteria did not need to be met). Results: 194, 023 ABSSSI encounters were identified, most receiving non-IV treatment (90%). 18, 603 received IV treatment, where 83% initially presented to the emergency room and the majority were admitted (97%). Of the 28 encounters with LAA use, 7 were inpatient. Of all current inpatient encounters ( N = 9, 019 after Jan 1, 2015), the majority ( N = 7, 005; 78%) where considered potential LAA pathway candidates. Comparing inpatient encounters with vs. without LAA use, mean LOS and cost differed (Table 2: 4.1 days and $14, 295 vs. 9.0 days and $23, 194, respectively). A sensitivity analysis supported similar mean LOS and cost for all inpatient LAA dispenses. Conclusion: Current use of LAA in an inpatient population is limited but resulted in potential cost-savings. Most of the inpatient population was identified as potential candidates for an outpatient LAA pathway. Research on utilization and quality of care for outpatient IV treatment pathways with LAA is warranted. Disclosures: K. R. Keyloun, Allergan: Employee,  Salary N. Bonine, Allergan: Employee, Salary